A method for preparing super hydrophilic carbon fiber
By assembling amino winding tannin on the surface of one-dimensional carbon fiber material to construct superhydrophilic functionalized carbon fiber material, the problem of lack of soft alkaline active sites on the surface of carbon fiber material is solved, and efficient recovery and selective adsorption of precious metals are achieved.
Patent Information
- Application Number
- CN202211405614.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-11-10
AI Technical Summary
The surface of one-dimensional carbon fiber materials lacks soft alkaline N and S active sites, and cannot be effectively applied to the field of precious metal recycling.
Through ammonia plasma treatment and glutaraldehyde crosslinking, amino groups were successfully assembled around tannin molecules on the surface of carbon fiber material to construct a superhydrophilic functional carbon fiber material.
Efficient adsorption and one-step reduction of Au(III) ions are achieved, which significantly improves the efficiency and selectivity of precious metal recycling, and ensures sustainable use of resources and environmental protection.
Smart Images

Figure CN115948909B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon fiber materials, and in particular to a method for preparing super hydrophilic carbon fiber. Background Art
[0002] Gold is an important strategic resource for the country and is widely used in high-tech fields, semiconductors, fine chemicals, jewelry and currency. The global supply of gold mainly comes from mining and development, accounting for about 75% of its total volume of use. At present, the grim fact facing mankind is that the natural resource reserves of high-quality gold-bearing ores are decreasing, and the demand for gold is increasing worldwide. However, in the process of gold mining, refining and processing, millions of cubic meters of gold-bearing wastewater (concentration less than 100ppm) are inevitably generated. The direct discharge of these gold-bearing wastewaters not only wastes precious rare resources, but also causes serious damage to the ecological system due to the strong oxidizing ability of Au(III) ions. Obviously, it is necessary for us to develop a new and sustainable strategy to recover gold-bearing wastewater and reuse Au(III) in gold-bearing wastewater.
[0003] Nowadays, various technologies such as electrochemistry, ion exchange, membrane separation, precipitation impregnation and adsorption have been developed and applied to separate and recover Au(III) ions from wastewater solutions. Among these technologies, the functional material adsorption method has been widely favored by researchers due to its outstanding advantages such as low cost, high efficiency, convenient operation, environmental friendliness and safety. According to the theory of hard and soft acids and bases, Au(III) is a typical soft acid that can chemically chelate with soft alkaline active sites (mainly including N-containing and S-containing functional groups). Therefore, the use of rich N-containing and S-containing active functional groups to modify low-surface-area materials has become the mainstream of Au(III) adsorbent construction.
[0004] One-dimensional carbon fiber materials have attracted increasing attention due to their ubiquity, easy availability, and large specific surface area. Previous studies have shown that carbon fiber materials have a high adsorption and removal efficiency for hydrophobic organic compounds. However, the surface of one-dimensional carbon fiber materials lacks soft alkaline N and S active sites, and their modification and use in the field of precious metal recovery have not been fully studied. Summary of the invention
[0005] The present invention aims to provide a method for preparing super hydrophilic carbon fiber to solve the problem that the surface of one-dimensional carbon fiber material cannot be applied to the field of precious metal recovery due to the lack of soft alkaline N and S active sites.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing super hydrophilic carbon fiber comprises the following steps:
[0008] S1. Synthesis of amino-modified carbon fiber materials:
[0009] 500 mg of carbon fiber was transferred to a plasma reaction bottle, and vacuum was repeatedly drawn and ammonia was introduced for cleaning 3 times. Under high vacuum conditions, an appropriate amount of ammonia was slowly introduced to stabilize the vacuum gauge reading at 50 Pa. The power matcher was turned on, and a high-frequency alternating current with a power of 50 W was introduced. Under electromagnetic stirring, the glow continued for 50 minutes to obtain an amino-modified carbon fiber material;
[0010] S2. Synthesis of aminorhodanine assembled carbon fiber materials:
[0011] 70 mg of amino-modified carbon fiber and 74 mg of aminorhodanine were mixed, dispersed in 20 ml of ultrapure water and stirred at 500 rpm for 2 hours; 1 ml of 50% glutaraldehyde aqueous solution was added to the stirred suspension, and then stirred at 500 rpm for 3 hours; after the aminorhodanine and plasma-modified carbon fiber were dispersed and mixed, they were stably grafted on the surface of the ammonia plasma-modified carbon fiber under the cross-linking action of glutaraldehyde; finally, they were centrifuged and washed three times with ultrapure water and anhydrous ethanol respectively, and then vacuum dried to obtain a carbon fiber material grafted with aminorhodanine small molecules.
[0012] Principle and effect of the technical solution: A new type of fiber material is synthesized by optimizing the chemical composition and physical composition of carbon fiber. N-aminorhodanine is used as a surface modifier of the fiber material because its molecular structure has abundant soft alkaline functional groups (such as -CS and -C=S), and it is used for selective adsorption and one-step reduction of Au(III) ions in solution. This solution provides a simple method for synthesizing a new type of fiber material for Au(III) recovery, which helps to ensure the sustainable use of resources and prevent environmental pollution.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] 1. Compared with other carbon material modification methods (typical wet chemical method: high temperature acid solution reflux), the plasma modification process (due to its simple operation, low cost, and no secondary pollution) is more cost-effective, convenient and feasible.
[0015] 2. This scheme successfully assembled aminorhodanine molecules on the surface of super-hydrophobic one-dimensional carbon fiber materials through NH3 plasma technology and glutaraldehyde cross-linking, constructed a novel functionalized carbon fiber material, and achieved the modification of its chemical composition and physical structure. The carbon fiber modification process is simple to operate, with mild reaction conditions, high yield and high modification efficiency. Direct calcination after adsorption can obtain high-purity gold.
[0016] 3. The carbon fiber material prepared by this scheme exhibits a high adsorption capacity for gold ions in the solution. When the solution pH = 4, the maximum adsorption capacity of the carbon fiber nanomaterial can reach 229 mg / g, which is 20.6 times that of the original carbon fiber (11.1 mg / g), and exceeds the gold ion adsorption performance of most carbon materials and their carbon-modified materials in the field.
[0017] 4. After the trivalent gold ions are adsorbed onto the surface of the modified carbon fiber material, about 44.3% of the trivalent gold ions are directly adsorbed and reduced to zero-valent gold nanoparticles in one step. Another advantage of using modified carbon fiber materials as adsorbents is that after the trivalent gold ions are adsorbed, they can be directly calcined at high temperatures, the carbon fiber material is converted into gas, and the trivalent gold ions obtain electrons, and together with the reduced nano-gold particles, they eventually remain in the crucible in the form of solid powder.
[0018] 5. Electronic waste treatment fluid and industrial wastewater contain a large number of competitive ions, such as Zn (II), Pb (II), Ni (II), and Cu (II). The modified carbon fiber material designed in this scheme also exhibits super selective adsorption ability in laboratory simulated wastewater (the concentration of gold ions and other competitive ions is 50 mg / L). Under different solution pH conditions (pH = 1 and pH = 4), the selective adsorption efficiency of modified carbon fiber materials for gold ions is greater than 96.24%; while the adsorption efficiency for other competitive ions (including: Zn, Pb, Ni, Cu) is less than 2%.
[0019] 6. The adsorption of trivalent gold ions by the modified carbon fiber designed in this scheme is a thermally driven process. When the ambient temperature is further increased to 55°C, the adsorption capacity of the modified carbon fiber for trivalent gold ions can be further increased to 328.8 mg / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The synthesis process of aminorhodanine modified carbon fiber in this embodiment;
[0021] Figure 2 Schematic diagram for explaining the changes in the surface chemistry and physical structure of the aminorhodanine-modified carbon fiber material in the embodiment;
[0022] Figure 3 This is a schematic diagram showing that the hydrophilicity of the three carbon fiber materials in this embodiment is improved after being sequentially treated;
[0023] Figure 4 The XPS full scan spectra of three different carbon fibers in this embodiment;
[0024] Figure 5 High-resolution refined spectra of N1s of three different carbon fiber materials in this example;
[0025] Figure 6 The contact angle test diagram of three different carbon fibers in this embodiment;
[0026] Figure 7 This is a graph showing the adsorption performance of three different carbon fibers to trivalent gold ions in this embodiment;
[0027] Figure 8 This is a diagram showing the selective adsorption of trivalent gold ions by aminorhodanine assembled carbon fibers in this example. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments:
[0029] like Figure 1-3 As shown, a method for preparing super hydrophilic carbon fiber comprises the following steps:
[0030] S1. Synthesis of amino-modified carbon fiber materials:
[0031] 500 mg of carbon fiber was transferred to a plasma reaction bottle, and vacuum was repeatedly drawn and ammonia was introduced for cleaning 3 times. Under high vacuum conditions, a certain amount of ammonia was slowly introduced to stabilize the vacuum gauge reading at 50 Pa. The power matcher was turned on, and a high-frequency alternating current with a power of 50 W was introduced. Under magnetic stirring, the glow lasted for 50 minutes to obtain amino-modified carbon fiber material.
[0032] S2. Synthesis of aminorhodanine assembled carbon fiber materials:
[0033] 70 mg of plasma-modified carbon fiber was mixed with 74 mg of aminorhodanine, dispersed in 20 ml of ultrapure water and stirred at 500 rpm for 2 hours; 1 ml of 50% by mass glutaraldehyde aqueous solution was added to the stirred suspension, and then stirred at 500 rpm for 3 hours; after the aminorhodanine and plasma-modified carbon fiber were dispersed and mixed, they were stably grafted on the surface of the ammonia plasma-modified carbon fiber under the cross-linking action of glutaraldehyde; finally, the carbon fiber material grafted with aminorhodanine small molecules was obtained after centrifugal washing with ultrapure water and anhydrous ethanol for 3 times respectively, and vacuum drying was performed.
[0034] By regulating the amount of ammonia introduced in this embodiment, controlling the duration of the glow and the glow energy, the number of amino groups introduced on the surface of the carbon fiber material can be further increased. The above regulation is a very important process, which makes the functionalization efficiency of the surface of the inert material higher and provides more grafting sites for the subsequent chemical modification of the surface of the carbon fiber material.
[0035] The properties of the aminorhodanine assembled carbon fiber material prepared in this example are as follows:
[0036] XPS Characterization:
[0037] XPS characterization was further performed in order to detect the chemical changes on the surface of the modified materials. Figure 4 As shown in the XPS spectrum, compared with the original carbon fiber material, in addition to the O1s and C 1s peaks, the XPS spectrum of the plasma-modified carbon fiber shows the 1s peak of the N element. This shows that the ammonia plasma treatment activates the surface of the inert carbon fiber material and introduces rich nitrogen-containing functional groups to the surface of the material. The N1s XPS refinement peak of the ammonia plasma-modified carbon fiber material shows (see Figure 2). Figure 5 In the middle a view), the two peaks at 399.91eV and 401.48eV can be attributed to -NH2 and -NH3 + This fully demonstrates that after the plasma glow reaction, ammonia is ionized to produce free radicals, which are eventually implanted on the surface of the original carbon fiber material in the form of -NH2. Figure 5 (b view in the middle), the N1s peak in its XPS spectrum shifted toward the direction of higher binding energy, and the NH2 peak corresponding to 400eV disappeared, indicating that the free amino groups on the surface of the ammonia plasma-modified carbon fiber material reacted chemically with glutaraldehyde during the process of grafting aminorhodanine. At this time, the two peaks of 399.96eV and 401.38eV are attributed to -C=N and CN. Among them, the -C=N double bond structure as a sign of the Schiff base structure proves the grafting principle of glutaraldehyde: the aldehyde group of the glutaraldehyde molecule undergoes an amidation reaction with the amino group on the surface of the precursor raw materials (ammonia plasma-modified carbon fiber and aminorhodanine), so that the aminorhodanine is grafted and assembled on the surface of the ammonia plasma-modified carbon fiber material in the form of a chemical bond. In addition, for the aminorhodanine assembled carbon fiber materials (such as the attached Figure 4 and attached Figure 5 (c view), the 2s and 2p peaks of the S element appear in the XPS spectrum. As characteristic elements of aminorhodanine, they directly prove that aminorhodanine is successfully grafted onto the surface of the material.
[0038] Contact angle test and hydrophilicity experimental characterization:
[0039] The differences in surface hydrophilicity of the three tested materials (original carbon fiber (carbon fiber initially added in step S1), amino-modified carbon fiber, and amino-rhodanine-assembled carbon fiber prepared in this embodiment) were detected and displayed in Figure 6 The contact angle of the original carbon fiber material is 142.48° (see attached Figure 6 (a) This shows that the original carbon fiber material has super hydrophobicity. After ammonia plasma modification, the contact angle of the ammonia plasma modified carbon fiber material is reduced to 95.9° (see Figure 2). Figure 6This is because ammonia plasma treatment introduces abundant polar functional groups (such as -NH2 and -NH3 + ), thereby enhancing the hydrophilicity of the carbon fiber material. It is worth noting that after aminorhodanine assembly, the contact angle of the carbon fiber material was reduced to 2.69° (as shown in the attached Figure 6 This indicates that after aminorhodanine containing O and N hydrophilic groups is grafted onto the surface of the carbon fiber material, the surface hydrophilicity of the carbon fiber material is significantly improved.
[0040] Performance test of aminorhodanine assembled carbon fiber adsorbent:
[0041] The adsorption properties of the original carbon fiber (the carbon fiber initially added in step S1), the amino-modified carbon fiber, and the amino-rhodanine assembled carbon fiber (N-AMCNFs) prepared in this embodiment for trivalent gold ions are shown in FIG. Figure 7 As shown. With the increase of equilibrium gold ion concentration in the solution, the adsorption of trivalent gold ions by the original carbon fiber, ammonia plasma modified carbon fiber, and aminorhodanine assembled carbon fiber prepared in this embodiment increases accordingly, and their adsorption capacities finally reach 11.1, 55, and 229 mg / g, respectively. That is, the maximum equilibrium adsorption capacity of aminorhodanine assembled carbon fiber prepared in this embodiment for trivalent gold ions is 4.1 and 20.6 times that of ammonia plasma modified carbon fiber and original carbon fiber, respectively.
[0042] Optional testing:
[0043] The aminorhodanine assembled carbon fiber material prepared in this embodiment also showed super selective adsorption ability in laboratory simulated wastewater (the concentration of gold ions and other competing ions was 50 mg / L) (such as attached Figure 8 That is, under different solution pH conditions (pH=1 and pH=4), the selective adsorption efficiency of the aminorhodanine modified carbon fiber material prepared in this embodiment for gold ions is greater than 96.24%, while the adsorption efficiency for other competing ions (including: Zn, Pb, Ni, Cu) is less than 2%.
[0044] The above is only an embodiment of the present invention, and common knowledge such as specific technical solutions or characteristics known in the implementation scheme is not described in detail here. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the technical solution of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing super hydrophilic carbon fiber, characterized in that: The steps include: S1. Synthesis of amino-modified carbon fiber materials: 500 mg of carbon fiber was transferred to a plasma reaction bottle, and vacuum was repeatedly drawn and ammonia was introduced for cleaning 3 times. Under high vacuum conditions, an appropriate amount of ammonia was slowly introduced to stabilize the vacuum gauge reading at 50 Pa. The power matcher was turned on, and a high-frequency alternating current with a power of 50 W was introduced. Under electromagnetic stirring, the glow continued for 50 minutes to obtain an amino-modified carbon fiber material; S2. Synthesis of aminorhodanine assembled carbon fiber materials: 70 mg of amino-modified carbon fiber and 74 mg of aminorhodanine were mixed, dispersed in 20 ml of ultrapure water and stirred at 500 rpm for 2 hours; 1 ml of 50% glutaraldehyde aqueous solution was added to the stirred suspension, and then stirred at 500 rpm for 3 hours; after the aminorhodanine and plasma-modified carbon fiber were dispersed and mixed, they were stably grafted on the surface of the ammonia plasma-modified carbon fiber under the cross-linking action of glutaraldehyde; finally, they were centrifuged and washed three times with ultrapure water and anhydrous ethanol respectively, and then vacuum dried to obtain a carbon fiber material grafted with aminorhodanine small molecules.
Citation Information
Patent Citations
Step-by-step modification of ultra high molecular weight polyethylene fiber and preparation method of compound material thereof
CN108330692A
Preparation method for tannic acid modified ultrahigh molecular weight polyethylene fibers and composite material thereof
CN108395675A